(3TQM JYdjbGJ YUGe Ydi GdeWhd aj Gdaf GdKGfis - (3EHQGgje Hf eMeO Hf YQH TGg GdESaQGjjfj, YUGe GdOjf , GdYUGe GdESaQGjjfj,J (B945 (3g` s ((3CMeO Hf SdjeGf s)
(3ChdgG (B:s
(3GdbGfhf GdChd ajeG jJYdb HGdNHQ bOe eHGMK GdNHQ GdSHbI ai GdEYJHGQ hPdc dchfg CbOe ai GdETJbGb hCcKQ ai GdESJYeGd hChaQ ai GdETJeGd s
(3BNQgG (B:s
(3chVY GdTGYQ ai bhdg (B: (3Ef JSGdhG GdMb HYWi GdMb SGFdI ajg hVY GdXGgQ ehVY VejQ GdZGFH ceG SjCJi JeJ GdcJGH HYhf Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hGdeWhd gh TQM JdNjU GdeaJGM ddJaJGRGfi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs